2021
DOI: 10.1088/1757-899x/1157/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic deep drawing of aluminum alloy AA6014 using macro-structured tools

Abstract: For functional lightweight construction, 6xxx aluminum alloys are essential materials for exterior components due to their low weight to stiffness ratio and acceptable formability. The formability of the 6xxx alloys is lower compared to other aluminum alloys but they are free of flow lines. MOUSAVI ET AL. [1] demonstrate an alternative method of improving the forming limit with a deep drawing process using macro-structured tools. Another approach increasing the formability of aluminum alloys is forming at cryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Subject of the study are numerical and experimental investigations regarding the formability of the aluminum alloy AA6014 in a deep drawing process with macro-structured tools at cryogenic blank temperatures. The object of this investigation is the increasing drawing ration of AA6014 and represents the continuation of the preliminary tests in [10]. It is assumed that the line contact between the macro-structured tools and the blank results in a reduction of the heat flux between tools and blank that enables deep drawing with improved material properties at cryogenic temperatures of the sheet metal.…”
Section: Macro-structured Deep Drawing Under Cryogenic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subject of the study are numerical and experimental investigations regarding the formability of the aluminum alloy AA6014 in a deep drawing process with macro-structured tools at cryogenic blank temperatures. The object of this investigation is the increasing drawing ration of AA6014 and represents the continuation of the preliminary tests in [10]. It is assumed that the line contact between the macro-structured tools and the blank results in a reduction of the heat flux between tools and blank that enables deep drawing with improved material properties at cryogenic temperatures of the sheet metal.…”
Section: Macro-structured Deep Drawing Under Cryogenic Conditionsmentioning
confidence: 99%
“…This leads to the question, if the combination of approaches results in an increasing process window. In [10] it was already shown that deep drawing of aluminum sheets with a sheet temperature in the cryogenic range with macro-structured tools leads to a reduction of the required punch force and spring back.…”
Section: Introductionmentioning
confidence: 99%